Taking economic, social and cultural rights seriously in international criminal law - Schmid, Evelyne (Cambridge studies in international and comparative law, 2015)
"Is the neglect of economic, social and cultural abuses in international criminal law a problem of positive international law or the result of choices made by lawyers involved in mechanisms such as criminal prosecutions or truth commissions? Evelyne Schmid explores this question via an assessment of the relationship between violations of economic, social and cultural rights and international crimes. Based on a thorough examination of the elements of international crimes, she demonstrates how a situation can simultaneously be described as a violation of economic, social and cultural rights and as an international crime. Against the background of the emerging debates on selectivity in international criminal law and the role of socio-economic and cultural abuses in transitional justice, she argues that international crimes overlapping with violations of economic, social and cultural rights deserve to be taken seriously, for much the same reasons as other international crimes"--